Presidential Threshold Dalam Sistem Pemilihan Presiden dan Wakil Presiden di Indonesia - Soselisa, Dodi L K; Pietersz, Jemmy Jefry; Nendissa, Renny Heronia (Postgraduate Program in Law, Pattimura University, 2024)
Introduction: With the presidential threshold setting in the current election law, it has limited the constitutional rights of political parties as stipulated in Article 6A paragraph (2) of the 1945 Constitution. The crisis over the constitutional rights of political parties. Purposes of the Research: Knowing and Analyzing the Presidential Threshold is a limitation on the constitutional rights of political parties.Methods of the Research: The research method used is juridical-normative, the legal materials used are primary and secondary using the following approaches: (i) statutory approach; (ii) contextual approach, (i) comparative approach; (iv) case approach and (v) historical approach.Results of the Research: The results of the study show that the Presidential Threshold setting in the Election Law is a limitation on the constitutional rights of political parties. Because if you look at the full design of Article 6A of the 1945 Constitution in the original intention, no statement or discussion is found that directly alludes to the implementation of the presidential threshold provision.